The Influence of Security, Easy, Benefits and Community Interest on The Use of Digital Payment as A Payment Tool in Jabodetabek - Justin, Justin; Yani Kusumastuti, Sri (Lafadz Jaya Publisher, 2022)
This study aims to analyze and test the variables of security, convenience, usefulness and public interest in the use of digital payment as a means of payment in Jabodetabek. This Study uses a qualitative method with purposive sampling technique. The population in this study is the user community of application-based digital payments such as DANA, GOPAY, OVO, SHOPEEPAY, SAKUKU, ISAKU, PAYTREN, DOKU, and LINKAJA. The number of samples is 233 respondents. The analysis method is a structural equation model. The result of this study show that security and public interest have a significant effect on the use of digital payments as a means of payment and for convenience and usefulness are not a benchmark for the community, especially at this time the impact of behavior who are used to make payments using digital payments.